PENGEMBANGAN VCD INSTRUKSIONAL PEREGANGAN AKTIF (ACTIVE STRETCHING) KESEGARAN JASMANI SISWA SMP DI MALANG - Peni Nohantiya (Multilateral : Jurnal Pendidikan Jasmani dan Olahraga, 2016)
Stretching is muscle extending that is done to prepare muscle of the body to make an activity and make our body relax after doing exercise. The student of Junior High School includes in the Spurt Grow age or grows up rapidly. And to support it, it needs high flexibility level. The function is to keep the flexibility of muscle. Besides, it help to make grow, flexibility or body refraction that is very useful to reduce hurt risk. Based on the characteristic of the student of Junior High School and the time limit of the lesson, the student need to do some stretching that is not take much time, but it can give an effect to  a whole body that is doing some active stretching. It called simple and save because this method is done alone without additional tool or friend. Active stretching is the most simple and save method. Stimulating the student in learning this exercise, it needs to make learning media that is interesting and easy to understand that is VCD. Kata kunci: Pengembangan, VCD Instruksional, Peregangan Aktif, Kesegaran Jasmani, Siswa SMP